2001
DOI: 10.1007/3-540-44759-8_65
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Classification and Description of Multidimensional Data Models

Abstract: Abstract. The words On-Line Analytical Processing bring together a set of tools, that use multidimensional modeling in the management of information to improve the decision making process. Lately, a lot of work has been devoted to modeling the multidimensional space. The aim of this paper is twofold. On one hand, it compiles and classifies some of that work, with regard to the design phase they are used in. On the other hand, it allows to compare the different terminology used by each author, by placing all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Most of the multidimensional models documented in the literature are based on business data (Abello et al, 2001) and thus may not meet the requirements of biomedical data warehousing. Pedersen et al (2001) evaluated 14 existing multidimensional models against the requirements of clinical data warehousing and found that none of these models support all the requirements.…”
Section: Application Of Existing Multidimensional Modelsmentioning
confidence: 99%
“…Most of the multidimensional models documented in the literature are based on business data (Abello et al, 2001) and thus may not meet the requirements of biomedical data warehousing. Pedersen et al (2001) evaluated 14 existing multidimensional models against the requirements of clinical data warehousing and found that none of these models support all the requirements.…”
Section: Application Of Existing Multidimensional Modelsmentioning
confidence: 99%
“…Transactional Processes (OLTP) and Online Analytical Processes (OLAP) [15]. Figure 11 summarizes these differences.…”
Section: Source Data Misconceptionsmentioning
confidence: 99%
“…In this work we apply a set of QVT [2] relations to the development of a secure DW. Various approaches for the conceptual design of the DW repository have been proposed in [4,5,6,7]. These proposals are twofold; on the one hand they try to represent the main MD properties at the conceptual level by abstracting away details of the target database platform where the DW will be implemented.…”
Section: Introductionmentioning
confidence: 99%